2014
DOI: 10.1259/bjr.20130503
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric post-septal and pre-septal cellulitis: 10 years' experience at a tertiary-level children's hospital

Abstract: We recommend that all patients with a suspected diagnosis of post-SC should undergo CT scan (post-contrast orbits and post-contrast head, with multiplanar reformats and a careful review of the SOV and the cavernous sinus). Particular attention should be paid to exclude intracranial complications including subdural empyema and cerebral abscess. As soon as a diagnosis of post-SC is made, in addition to informing the referring clinical team, urgent opinion should be sought from ear, nose and throat (ENT), neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Neither ultrasound nor MRI was prescribed in our study. In majority of the studies, sinusitis especially ethmoidal ones were a main predisposing factor [4,6,11,14,18,19,29]. This matches our study where sinusitis dominated (29%) where ethmoid sinusitis came rst (63%).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Neither ultrasound nor MRI was prescribed in our study. In majority of the studies, sinusitis especially ethmoidal ones were a main predisposing factor [4,6,11,14,18,19,29]. This matches our study where sinusitis dominated (29%) where ethmoid sinusitis came rst (63%).…”
Section: Methodssupporting
confidence: 89%
“…Whiles they're important in retroseptal cellulitis and that can lead to visual complications even fatal ones. It can be di cult to differentiate the two forms; consequently, paraclinical examinations are necessary to con rm the diagnosis and evaluate the complications [2,18,19]. The Chandler classi cation gives us a bene t of precising the infection's stage [2].…”
Section: Methodsmentioning
confidence: 99%
“…Blindness could happen in approximately 1% of patients with orbital cellulitis [1] . Nageswaran et al found that 98% of their patients with orbital cellulitis were affected by ethmoidal sinusitis and 71% by maxillary sinusitis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Howe and Jones recommended a computer tomography scan to be performed in patients where full evaluation of the eye is not possible because of gross edema, gross proptosis, opthalmoplegia, deteriorating visual acuity or color vision or bilateral periorbital oedema [1] . Nevertheless, even if preseptal cellulitis is presented, CT scan is recommended due to the rapid progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation